Americanised Pronunciation in British Rock Music on the Basis of the Vocal Styles of the Bands Bring Me The Horizon and Arctic Monkeys - Moćko, Wiktoria (Uniwersytet Warszawski, 2024)
Konert-Panek, Monika Bałaga-Rubaj, Monika Konert-Panek, Monika